Additive effects of anticoagulants: recombinant human activated protein C and heparin or melagatran, in tissue factor-activated umbilical-cord plasma - Koestenberger, Martin; Gallistl, Siegfried; Muntean, Wolfgang; Leschnik, Bettina; Fritsch, Peter; Cvirn, Gerhard (Thrombosis and Haemostasis, 2005)
Severe sepsis in children or adults may cause a life-threatening coagulopathy, with widespread consumption of activated protein C (APC); recombinant human APC (rhAPC) is a promising candidate anticoagulant treatment. We investigated the effects of rhAPC and other anticoagulants on coagulation triggered by adding small quantities of lipidated tissue factor to human umbilical-cord plasma in vitro. rhAPC, unfractionated heparin (UH),and melagatran (a direct thrombin inhibitor) were studied individually, and in combinations of rhAPC with either UH or melagatran. rhAPC alone dose-dependently prolonged the activated partial-thromboplastin time (aPTT) but not the prothrombin time (PT), and dose-dependently suppressed two indices of thrombin generation, namely prothrombin fragment F 1.2 (F 1.2) generation and thrombin–antithrombin (TAT) complex formation. UH alone dose-dependently prolonged the aPTT but not the PT, while melagatran alone dose-dependently prolonged both the aPTT and the PT. Adding either UH or melagatran dose-dependently augmented the capacity of rhAPC to suppress F 1.2 generation (with addition of UH showing a greater effect) and TAT formation (with addition of melagatran showing a greater effect). Both the capacity of UH to prolong the aPTT and the capacity of melagatran to prolong the aPTT and the PT were augmented by adding rhAPC. In our in-vitro study, adding either UH or melagatran augmented the capacity of rhAPC to suppress thrombin generation in human umbilical-cord plasma, with the anticoagulant effect of melagatran being more predictable than that of UH. Hence, combining rhAPC with melagatran might be a valuable therapeutic option in patients with severe sepsis.
Keywords: Anticoagulation; heparin; melagatran; recombinant human activated protein C; thrombin